2019
DOI: 10.6018/eglobal.19.1.360321
|View full text |Cite
|
Sign up to set email alerts
|

Controlo da asma infantil: principais fatores asociados

Abstract: Introducción: El asma aparece como una enfermedad inflamatoria crónica de las vías respiratorias y se caracteriza por episodios de obstrucción bronquial reversible pudiendo ser desencadenada por varios factores. Se constituye como la enfermedad infantil más común, una importante causa de internamiento hospitalario y un problema de salud pública. Las directrices internacionales sobre la gestión del asma reconocen que el tratamiento reside en el control actual y en el riesgo de exacerbaciones, basándose en la ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This result could be justified by the reason that mother adherence to therapeutic regimen controlling the recurrence attack of bronchial asthma for their children. The findings of Sousa Félix et al, (2020) were in the same line with the present findings, who stated that more than one half of children were partially controlled recurrence asthma while more than one third of them were controlled recurrence asthma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result could be justified by the reason that mother adherence to therapeutic regimen controlling the recurrence attack of bronchial asthma for their children. The findings of Sousa Félix et al, (2020) were in the same line with the present findings, who stated that more than one half of children were partially controlled recurrence asthma while more than one third of them were controlled recurrence asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Tool III: Childhood Asthma Control Test and the Occurrence of Recurrent Attacks: It was developed by Sousa Félix et al, (2020) to assess asthma control in children 4-11 years old. It comprised of seven questions (4 for child and 3 for caregiver), The child-reported questions, rated on a 4-point Likert scale, contains daytime and activity limitation, nocturnal awakenings, and self-perceptions of asthma; the caregiver-reported questions, rated on a 6-point Likert scale, contains ask about the child's daytime and nocturnal symptoms.…”
Section: Materials and Methodmentioning
confidence: 99%
“…This shows its multifactorial nature and the complexity of its psychosocial effects. 5,6 It was found that negative family bio-behavioral factors contributed to the severity of asthma in children. 3 It is important to understand the contextual system that reflects the two-way relationship between children with asthma and their families because of its relation to children's well-being.…”
Section: Discussionmentioning
confidence: 99%